Deep multi-query video retrieval - VURAL, CABİR (My University, 2022)
© 2022 Elsevier Inc.Video retrieval methods have been developed for a single query. Multi-query video retrieval problem has not been investigated yet. In this study, an efficient and fast multi-query video retrieval framework is developed. Query videos are assumed to be related to more than one semantic. The framework supports an arbitrary number of video queries. The method is built upon using binary video hash codes. As a result, it is fast and requires a lower storage space. Database and query hash codes are generated by a deep hashing method that not only generates hash codes but also predicts query labels when they are chosen outside the database. The retrieval is based on the Pareto front multi-objective optimization method. Re-ranking performed on the retrieved videos by using non-binary deep features increases the retrieval accuracy considerably. Simulations carried out on two multi-label video databases show that the proposed method is efficient and fast in terms of retrieval accuracy and time.
Keywords: Harita Mühendisliği-Geomatik; Bilgi Sistemleri, Haberleşme ve Kontrol Mühendisliği; Sinyal İşleme; Bilgisayar Bilimleri; Algoritmalar; Mühendislik ve Teknoloji; Geotechnical Engineering; Information Systems, Communication and Control Engineering; Signal Processing; Computer Sciences; algorithms; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Bilgisayar Bilimi; Mühendislik; BİLGİSAYAR BİLİMİ, YAPAY ZEKA; MÜHENDİSLİK, ELEKTRİK VE ELEKTRONİK; MÜHENDİSLİK, ÇOK DİSİPLİNLİ; Engineering, Computing & Technology (ENG); COMPUTER SCIENCE; ENGINEERING; COMPUTER SCIENCE, ARTIFICIAL INTELLIGENCE; ENGINEERING, ELECTRICAL & ELECTRONIC; ENGINEERING, MULTIDISCIPLINARY; Fizik Bilimleri; Medya Teknolojisi; Bilgisayarla Görme ve Örüntü Tanıma; Elektrik ve Elektronik Mühendisliği; Physical Sciences; Media Technology; Computer Vision and Pattern Recognition; Electrical and Electronic Engineering; Multi-query video retrieval; Pareto optimization; Video hashing